2010
DOI: 10.1590/s1516-35982010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrientes em folhas diagnósticas do capim-tanzânia adubado com nitrogênio e cálcio

Abstract: RESUMO -Um experimento foi realizado em casa de vegetação com capim-tanzânia adubado com combinações de nitrogênio e de cálcio em solução nutritiva no período da primavera. O delineamento estatístico foi de blocos ao acaso, com quatro repetições, em esquema fatorial 5 2 incompleto, com cinco doses de nitrogênio (2; 9; 16; 23 e 30 mmol L -1 ) e cinco de cálcio (0,50; 1,75; 3,00; 4,25 e 5,50 mmol L -1 ), resultando em 13 combinações nitrogênio:cálcio (mmol L -1 ): 2:0,50; 2:3,00; 2: 5,50; 9:1,75; 9:4,25; 16:0,50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…It is worth pointing out that the cultivar Tanzania absorbs the lowest Mg contents when irrigated with fish farming effluent in the first, second and third cuts, compared to the others, with contents of 4.34, 6.26 and 8.09 g Mg kg -1 of dry matter, respectively. However, the values obtained for Tanzania grass are higher than those found in the literature, which range from 1.8 to 2.5 g (Mg) kg -1 of dry matter (SILVEIRA; MONTEIRO, 2010). The high Mg contents observed in P. maximum cultivars can be explained by the high concentrations of Mg in Table 6.…”
Section: Resultsmentioning
confidence: 58%
“…It is worth pointing out that the cultivar Tanzania absorbs the lowest Mg contents when irrigated with fish farming effluent in the first, second and third cuts, compared to the others, with contents of 4.34, 6.26 and 8.09 g Mg kg -1 of dry matter, respectively. However, the values obtained for Tanzania grass are higher than those found in the literature, which range from 1.8 to 2.5 g (Mg) kg -1 of dry matter (SILVEIRA; MONTEIRO, 2010). The high Mg contents observed in P. maximum cultivars can be explained by the high concentrations of Mg in Table 6.…”
Section: Resultsmentioning
confidence: 58%
“…Isso se deve ao fato que, de todo o nitrogênio presente na parte aérea formada na primeira semana após o corte das plantas, 80% pode ser proveniente da translocação do nitrogênio a partir das raízes e dos colmos e o restante proveniente da absorção de nitrogênio (Chapman & Lemaire, 1996). Assim, o suprimento de nitrogênio para a parte aérea (Silveira & Monteiro, 2010) fica dependente de um sistema radicular mais desenvolvido.…”
Section: Resultsunclassified
“…According to Marschner and Marschner (2012), the nutrient supply can influence root system growth and distribution, and this effect is marked mainly by N. In addition, Silveira and Monteiro (2010) reported that the N supply to the aerial part is dependent on a well-developed root system.…”
Section: Discussionmentioning
confidence: 99%